2022
DOI: 10.1002/alz.067302
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging longitudinal, multi‐site diffusion MRI data in conjunction with free‐water analysis to characterize patterns of white matter neurodegeneration in aging

Abstract: BackgroundSeveral prior studies have used diffusion MRI to investigate the relationship between white matter microstructure and aging; however, many of these studies used conventional diffusion MRI measures and single site data. The goal of the study is to leverage multi‐site harmonized diffusion MRI data in conjunction with a novel post‐processing technique [i.e., free‐water (FW) correction] to quantify the aging related tract‐specific changes in white matter microstructure.MethodThe dataset used in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Projection tracts connect the cortex to subcortical structures and help integrate sensory, motor, and cognitive functions.Our findings support previous cross-sectional work that found that females had lower FA values in sensory and motor projections 10 and a greater decline in FA over time compared to males. 11 Previous work has consistently found that association tracts are affected in the aging process 10,28 and these tracts show a greater decline in FA and FA FWcorr in individuals with cognitive impairment relative to cognitively unimpaired adults. 28,53 While some studies have shown that projection fibers are also associated with abnormal cognitive aging, these associations are less robust.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Projection tracts connect the cortex to subcortical structures and help integrate sensory, motor, and cognitive functions.Our findings support previous cross-sectional work that found that females had lower FA values in sensory and motor projections 10 and a greater decline in FA over time compared to males. 11 Previous work has consistently found that association tracts are affected in the aging process 10,28 and these tracts show a greater decline in FA and FA FWcorr in individuals with cognitive impairment relative to cognitively unimpaired adults. 28,53 While some studies have shown that projection fibers are also associated with abnormal cognitive aging, these associations are less robust.…”
Section: Discussionmentioning
confidence: 96%
“…11 Previous work has consistently found that association tracts are affected in the aging process 10,28 and these tracts show a greater decline in FA and FA FWcorr in individuals with cognitive impairment relative to cognitively unimpaired adults. 28,53 While some studies have shown that projection fibers are also associated with abnormal cognitive aging, these associations are less robust. 10,28,49 Given that females are disproportionately affected by AD, the observed sex differences in FA FWcorr in our study suggest that white matter integrity may contribute to this disparity.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations